Dynamics of Anti-Oxidant Levels and Activities of Reactive Oxygen-Scavenging Enzymes in ‘Pink Lady’ Apple Fruit during Maturation and Ripening - Abbasi, Nadeem; Singh, Zora; Khan, Ahmad (Pakistan Botanical Society, 2010)
‘Pink Lady’ apple fruit were evaluated for anti-oxidative stress at various stages of fruit maturity and ripening. Fruit were harvested at weekly intervals starting 7 days before anticipated commercial harvest up to 42 days after commercial harvest (DACH), and then fruit harvested at commercial maturity were allowed to ripen at 22 ± 0.5oC for 20 days. Ethylene production and respiration rate increased with advancing fruit maturity. Fruit firmness and titratable acidity (TA) decreased, whilst SSC and SSC:TA ratio increased with increase in fruit maturity and ripening. A significant decline in SOD (SOD; EC 1.15.1.1) activity in fruit harvested on 21 and 28 DACH wasdetected in fruit skin and pulp tissues and then SOD activity increased. During fruit ripening period, skin and pulp tissue also exhibited a similar trend in SOD activity. A significant increase in the activity of catalase (CAT, EC 1.11.1.6) enzyme was observed in the fruit skin and pulp tissue during fruit maturation and ripening. ‘Pink Lady’ apple fruit exhibited appreciable levels of SOD and CAT activities harvested during extended period of fruit harvest maturity and subsequent fruit ripening.